Scope of Consumer Protection in the Payment Protection Insurance Offered by Selected Banks - Nowak, Katarzyna (Journal of Finance and Financial Law, 2020)
It is common practice in the financial market for banks to combine credit with insurance in their offers. Credit insurance is a combination of two financial services – a banking and an insurance service Insurance distribution with loans is a natural phenomenon. Credit and insurance are complementary products. Instalment is generally a serious expense in the household budget. As a consequence of taking out a loan, risk of losing borrower’s ability to fulfill financial obligations increase. With this end in view borrower has insurance as an instrument to defusing the risk of borrowing. Banks treat an insurance agreement as a collateral for the repayment of a loan, which is an additional security. On the other hand this instrument can be helpful for the consumer financial difficulties due to work loss or permanent disability. The purpose of insurance added to loan is to reduce the risk of the borrower's inability to repay the loan and to ensure the safety of the insured or beneficiary of insurance policy. Insurance is not a typical product on the financial market because the policy holder acquires an abstract guarantee of insurance benefit in exchange for an insurance premium.The aim of the article is to compare and assess insurance the scope of consumer (policyholder) protection based on general insurance conditions in payment protection insurance added to consumer loan offered by the two largest banks in Poland. Comparative analysis of the scope of consumer was based on this few category: subject matter of insurance, definition of event covered by the insurance company, type of insurance benefit and exclusions and limitations of lability.